2017
DOI: 10.1016/j.jcat.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling water effects on solid acid catalysts: Case study of TiO 2 /SiO 2 as a catalyst for the dehydration of isobutanol

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 72 publications
5
64
1
Order By: Relevance
“…It revealed that amorphous SnO 2 clusters were reduced to Sn crystalline particles under isobutanol vapour at 300 °C leading to dehydrogenating activity. High conversion (89.3%) and very high selectivity to butenes (97.4%) was obtained using 20.4%TiO 2 /SiO 2 -G after 4 h. Such feature was in agreement with data obtained in the same conditions of temperature and contact time but with a diluted feed iC 4 OH/inert: 35/65 [44]. The isomerisation activity was slightly higher than the SiO 2 -G one (S LinBut 33% instead of 30%) and close to values reported in the literature for mixed oxides [24].…”
Section: Acidity Measurementssupporting
confidence: 89%
See 3 more Smart Citations
“…It revealed that amorphous SnO 2 clusters were reduced to Sn crystalline particles under isobutanol vapour at 300 °C leading to dehydrogenating activity. High conversion (89.3%) and very high selectivity to butenes (97.4%) was obtained using 20.4%TiO 2 /SiO 2 -G after 4 h. Such feature was in agreement with data obtained in the same conditions of temperature and contact time but with a diluted feed iC 4 OH/inert: 35/65 [44]. The isomerisation activity was slightly higher than the SiO 2 -G one (S LinBut 33% instead of 30%) and close to values reported in the literature for mixed oxides [24].…”
Section: Acidity Measurementssupporting
confidence: 89%
“…The isomerisation activity was slightly higher than the SiO 2 -G one (S LinBut 33% instead of 30%) and close to values reported in the literature for mixed oxides [24]. It is worth noting that a value of 33% was also measured at 300 °C for feed composition iC 4 OH/inert 35/65 and 1/WHSV 0.30 h [44]. After 20 h on stream, the conversion was lowered to 64.8% which corresponded to a faster deactivation than for a diluted feed [44].…”
Section: Acidity Measurementssupporting
confidence: 85%
See 2 more Smart Citations
“…At the reduction temperature of 500 °C, the catalyst showed no obvious peaks detected, indicating the most of Co 3 + were reduced into Co metal. The NH 3 -TPD results showed that in low reduction temperature, most of the Lewis sites of Co 3 O 4 were weak, since NH 3 as a strong base was able to react with them to form ammonium cations [33] . The atom percentage of O and Co elements was calculated by using EDS analysis during TEM measurements and the results are summarized in Table 2 .…”
Section: Catalyst Characterizationmentioning
confidence: 98%